Medical semiotics in the telemedicine era: The birth of telesemiotics. (January 2022) - Brizio, Albert; Faure, Valérie; Baudino, Franck
Graphical abstract: Abstract: Background: Telemedicine and videoconferencing distance examination are new and growing swiftly. Distance alters the patient-physician diagnostic context interfering with the traditional methods used to collect and interpret medical signs, introducing new constraints and opportunities. This study is an early contribution to the exploration of the changes in medical semiotics introduced by telemedicine. Objective: The main objective is to characterize the impact of telemedicine on medical semiotics and to analyze its consequences on distance medical examination. Methods: On empirical bases, an inductive reasoning was built on the observation of telemedical practice and personal experience analysis and supported by the research of existing models and literature. Results: The impossibility to touch the patient is the main constraint of telemedicine. While history taking and listening to the patient's symptoms depend on videoconferencing technology, for physical inspection, two main options exist: a helper-mediated physician-patient interaction and a direct physician-patient interaction without third-party intervention. In the latter case, the physician has to rely either on devices and-or on the patient becoming the physician's hands. This enhances the physician-patient partnership in the diagnostic process increasing the role of communication and means that the diagnostic tests usually performed by the physician need to be transformed to allow self-execution. Paradoxically, modern distance examination imposes a return to classical semiotics and puts the patient at the very core of the examination process through his/her active participation. The live use of connected medical devices and the direct access to computer facilities offer new opportunities for improved signs gathering and synchronous medical collaboration. Conclusion: We define telesemiotics, a special branch of medical semiotics mostly centered on self-performed physical examination, improved physician-patient communication and the use of computer facilities, that needs to become an integral part of medical training. It is hypothesized that the multiplication of empowered patients, actors of their own health, physically and intellectually participating in the diagnostic process, may lead to deep positive public health and societal repercussions.